2022
DOI: 10.1007/s12649-022-01958-9
|View full text |Cite
|
Sign up to set email alerts
|

Valorizing Kraft Lignin by a Catalytic Reductive Depolymerization in Ethanol/Water with Formic Acid as a Supplementary H2 Donor

Abstract: Lignin is a promising biopolymer to serve as a sustainable resource for a multitude of applications (e.g., thermoset materials, production of bulk chemicals) thereby substituting fossil-based carbon sources. In this work, the reductive depolymerization of Kraft lignin (KL) was studied in ethanol/water aided by formic acid (FA) as the way forward to valorize lignin. The effect of various process conditions was elucidated using 31 P-NMR, pH, GPC, CHNSO, GC-MS and 2D-LC analyses. It is found that the addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…This aligns with the literature, where Pd catalyzed lignin depolymerizations consistently outperform solvolysis (0Cata and Al 2 O 3 ). 11,12,20,23,41…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This aligns with the literature, where Pd catalyzed lignin depolymerizations consistently outperform solvolysis (0Cata and Al 2 O 3 ). 11,12,20,23,41…”
Section: Resultsmentioning
confidence: 99%
“…The derivatization with TMDP and analysis were based on the literature and the data processing was performed using TopSpin v4.2.0. 23 Phase and base line correction were performed automatically and the sharp peak of TMDP and H 2 O on the right side of the spectra was manually set to 132.2 ppm. The following integration ranges were applied: NHND (151.5–152.5 ppm), aliphatic OHs (145.2–150.0 ppm), condensed aromatic OHs (140.0–144.8 ppm, with subtraction of the syringyl aromatic OHs between 143.1 and 142.3 ppm), uncondensed aromatic OHs (137.0–140.4 ppm) and carboxylic acids (133.5–136.0 ppm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was elucidated that the temperature (in combination with Pd/Al 2 O 3 ) played an important role in the decomposition of formic acid with only a limited decomposition at 200 °C compared to 250 °C. 287…”
Section: Green Methods To Adjust the Types Of Oh Groups In Lignin And...mentioning
confidence: 99%
“…Additionally, it was elucidated that the temperature (in combination with Pd/Al 2 O 3 ) played an important role in the decomposition of formic acid with only a limited decomposition at 200 °C compared to 250 °C. 287 A cheap alternative to the use of noble metals was investigated by Lou et al They used LaBO 3 (B = Co, Fe or Ni) to convert AL to aromatics in MeOH-assisted hydrothermal liquefaction (80 °C-260 °C) and concluded that all the perovskite catalysts promoted the lignin treatment, but LaCoO 3 showed the highest catalytic performance. 288 Recently, Xu et al explored an ultrasonic-assisted method (250 °C, 6 h) as a greener and more efficient heating process with LaNiO 3 supported by a mesoporous carrier in ethanol/water (1/1 v/v) of corn stover lignin, resulting in a bio-oil yield of 68.0 wt% and phenolic monomer yield of 11.46 wt%.…”
Section: Reductive Depolymerizationmentioning
confidence: 99%